Sinergi Sains dan Syariat: Urgensi Tes DNA Sebagai Alat Bukti Primer dalam Perkara Pembatalan Perkawinan Inses - Mawaddah Rahma; Savitri Savitri; Asyifa Khoirunnisa; Daffa Rahel Zaida (INDO PUBLISHING, 2026)
Inbreeding (incest) is strictly prohibited by Islamic Sharia and Law No. 1/1974 because it violates fitrah and endangers the family structure and the health of the offspring. However, annulments of incestuous marriages in Religious Courts often fail due to the weakness of conventional evidence (witnesses and letters) that are unable to uncover biological truths due to invalid documentation or the closure of family facts. This article examines the urgency of integrating DNA tests as primary evidence through a forensic science approach and Maqasid al-Sharia analysis. The results of the study show that the DNA test has very accurate scientific validity to determine the fate and is in line with the purpose of the sharia in preserving the offspring (Hifz al-Nasl) and preventing damage (Mafsadah). community.